Stranding events of southern right whales, Eubalaena australis, in southern Brazil - B. Greig, Antonio; R. Secchi, Eduardo; N. Zerbini, Alexandre; Dalla Rosa, Luciano (J. Cetacean Res. Manage., 2020)
Although international protection has been granted since 1935, southern right whales have only recently shown signs of recovery, possibly due to anthropogenic factors. Off Brazil, illegal hunting of right whales occurred until 1973. This paper reports on surveys conducted along the southern Brazilian coast and the information recovered on right whale strandings for this area from 1977-1995. In the first 10 years of this period only four cases were registered. However, in contrast, 20 cases were counted during the last nine years. These results are discussed in relation to marine traffic and the fisheries in the area that produce risks of collision and entanglement. Further, the possibility of storm surges being a preponderant factor in the mortalities in this area is presented. These yearly rates are compared with neighbouring areas that are also inhabited by the right whales. Both possibilities fit the hypothesis that the right whales using the Brazilian coast for breeding may finally be showing signs of recovery.